The effect of strategic leadership and innovative organizational climate on employees' voice with the mediating role of work ethic maturity - Jafar Beikzad; Maryam Razmjou (مدیریت و چشم انداز آموزش)
Abstract The present study was conducted with the aim of providing a structural model of the impact of strategic leadership and innovative organizational climate on the voice of employees with the mediating role of work ethic maturity in vocational universities of West Azerbaijan province. This research is applicable in terms of purpose, and descriptive-correlative in terms of method. The statistical population of the research includes 156 employees of vocational universities of West Azerbaijan province, of which 111 people were selected as a statistical sample based on Cochran's formula by stratified random sampling. The data collection tool in this research includes 4 standard questionnaires. In order to ensure the existence or non-existence of a causal relationship between the research variables and to check the suitability of the observed data with the conceptual model of the research, the research hypotheses were tested using the structural equation model and the partial least squares method (PLS3). The findings of the research showed that strategic leadership has a significant effect on the voice of employees and the maturity of work ethics; and innovative organizational climate has a significant effect on the voice of employees and the maturity of work ethics. In addition, at the 99% confidence level, work ethic maturity plays a mediating role in the impact of strategic leadership and innovative organizational climate on employee voice. Extended abstract Introduction In today's competitive environment, managing organizations by means of a strategic leadership approach is not only a good idea, but a requirement for success and sustainability in the performance of any organization (Rezaei Manesh et al, 2023). Strategic leadership involves the use of strategies. Strategic leaders can influence organizational outcomes through their personal choices (Poursadeq & Qaraei Ashtiani, 2023). On the other hand, one of the organizational factors that can make strategic leadership effective is the innovative organizational climate. Organizational atmosphere is very effective in creating dynamism and creativity of an organization, especially educational organizations that deal with people. As a result, when there is a suitable atmosphere in the organization, people are more motivated to innovate because they work in an organization that accepts creativity and innovation by facilitating a suitable and dynamic atmosphere (Roudgarnezhad, 2023). In today's business environment, employee voice is a key component for increasing organizational competitiveness because it drives innovative ideas, enables error correction, and improves competitive advantage. In addition to organizational benefits, employee voice behavior also leads to higher performance evaluations and has a positive result in professional growth (Poorghafari et al, 2023). On the other hand, in analyzing the behavior of organizations, dealing with ethics and moral values ​​is one of the requirements. The external symbol of organizations is formed by their ethical behaviors, which itself is the sum of various values ​​of moral maturity (Jafari & Ghayor Baghban, 2024). Therefore, the main question of the current research is: whether strategic leadership and innovative organizational climate are effective on the voice of employees with emphasizing the mediating role of work ethic maturity in vocational universities of West Azerbaijan province. Theoretical framework Strategic leadership: Strategic leadership is a type of leadership style that explains the behavior of top managers and includes combining strategic thinking with strategic action and transferring this achievement to a strategic path and making strategic change (Poursadeq & Qaraei Ashtiani, 2023). Innovative organizational climate: Innovative organizational climate is an atmosphere that keeps the ability to accept an opinion or behavior new to the industry, market or general environment of the organization, grow and expand creative and innovative efforts in organizations, and facilitate learning (Roudgarnezhad, 2023). Employee voice: Although the argumentative background of employee voice can be traced back to two centuries ago, the initial concept of employee voice was developed in Harishman's (1970) theory of "exit, protest, and loyalty". He stated that employees react to unpleasant situations by leaving the organization or expressing their dissatisfaction (Poorghafari et al, 2022). Maturity of work ethics: Maturity of work ethics in the organization is the key to the ethical behavior of employees. In organizations that emphasize the maturity of work ethics, employees can work professionally (Ichsan et al, 2022). Methodology The current research is applicable in terms of purpose, and descriptive-correlative in terms of method. The statistical population of the research was 156 employees of vocational universities of West Azerbaijan province. The size of the statistical sample was estimated to be 111 people based on stratified random sampling and according to Cochran's formula. The data collection tool in this research includes 4 questionnaires. The data analysis of the current research was done using the structural equation modeling method based on PLS3 software, the results of which are presented in the research findings section. Face validity was used to calculate the validity of the research tool, which was approved by professors and experts. Cronbach's alpha coefficient has been used in order to analyze the reliability of the research tool. Discussion and Results The results of data analysis showed that the path coefficient between the two variables of strategic leadership and employee voice is β=0.942; and the significant coefficients between these two variables are p=0.000 and t=29.699, which shows that strategic leadership has an effect on the voice of employees, and therefore the first hypothesis is confirmed. The path coefficient between the two variables of strategic leadership and work ethic maturity is β=0.118; and the significant coefficients between these two variables are p=0.001 and t=5.834, which shows that strategic leadership has an effect on the maturity of work ethics, and therefore the second hypothesis is confirmed. The path coefficient between the two variables of innovative organizational climate and employees' voice is β=0.168; and the significant coefficients of these two variables are p=0.000 and t=2.674, which shows that the innovative organizational climate has an effect on the voice of employees, and therefore the third hypothesis is also confirmed. The path coefficient between the two variables of innovative organizational climate and work ethic maturity is β=0.732; and the significant coefficients between these two variables are p=0.000 and t=12.449, which shows that the innovative organizational climate has an effect on the maturity of work ethics, and therefore the fourth hypothesis is confirmed. The path coefficient between the two variables of work ethic maturity and employees' voice is β=0.849; and the significant coefficients between these two variables are p=0.002 and t=4.153, which shows that the maturity of work ethics has an effect on the voice of employees, and therefore the fifth hypothesis is confirmed. Also, the results indicated that the z-value of the Sobel test in the sixth and seventh hypotheses is equal to 2.673 and 3.250, respectively, which is more than 1.96; so at the confidence level of 99%, the maturity of work ethics plays a mediating role in the influence of strategic leadership and innovative organizational climate on the voice of employees. Conclusion This research was conducted with the aim of providing a structural model of the impact of strategic leadership and innovative organizational climate on the voice of employees with the mediating role of work ethic maturity in vocational universities of West Azerbaijan province. Statistical analysis and experiment and data analysis of the current research were done at two descriptive and inferential levels and with SPSS and PLS3 statistical software; and detailed outputs were analyzed and documented based on related figures and tables. According to the findings of the research, strategic leadership has a positive effect on the voice of employees, and also the positive effect of strategic leadership on the maturity of work ethics was confirmed. On the other hand, the results of the research showed that the innovative organizational climate has a positive effect on the voice of employees. Also, the positive effect of innovative organizational climate on maturity of work ethics was confirmed. Another result of the research was that the maturity of work ethics plays a mediating role in the influence of strategic leadership and innovative organizational climate on the voice of employees. Therefore, it can be said that strategic leadership, innovative organizational climate, organizational voice, and work ethics interact together and can jointly help improve organizational performance, increase employee job satisfaction, and create a positive organizational culture. In fact, strategic leaders can strengthen the work ethics culture in the organization by formulating and promoting ethical principles and organizational values. These leaders create a good role model for employees by demonstrating ethical and responsible behaviors. On the other hand, an innovative organizational climate can lead to an increase in organizational voice, because employees in an environment that values ​​innovation and creativity are more inclined to express their opinions and ideas and adhere to more ethical behaviors.